2006
DOI: 10.1002/pits.20142
|View full text |Cite
|
Sign up to set email alerts
|

Social support in inclusive middle schools: Perceptions of youth with learning disabilities

Abstract: This cross-sectional study examined the perceptions of social support reported by middle-school students with multiple learning disabilities (LD) (reading ϩ math) in inclusive settings. Comparison groups included youths with a learning disability in reading only (RD), mathematics only (MD), and no LD (i.e., normally achieving) (NA). One hundred twenty middle-school students, 15 boys and 15 girls in each group, were included in the current study. Participants were surveyed using an established measure of percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 47 publications
4
21
0
3
Order By: Relevance
“…This finding is consistent with the results reported by Martínez (2006) who found students Note. Path coefficients are standardized and significant at *p < .05, **p < .01, ***p < .001.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with the results reported by Martínez (2006) who found students Note. Path coefficients are standardized and significant at *p < .05, **p < .01, ***p < .001.…”
Section: Discussionsupporting
confidence: 93%
“…Those with RD and an additional difficulty tend to exhibit more academic and social difficulties (Willcutt et al, 2007) and score higher in sense of inadequacy and lower in perceived social support than those with one or no LD (Martínez, 2006). These findings suggest students with multiple disabilities are at increased risk for negative outcomes as young adults (Willcutt et al, 2007).…”
Section: Number Of Difficulties In Addition To Rdmentioning
confidence: 89%
“…Some commentators suggest that special schools provide an advantage over mainstream schools, as teachers are more aware of disabilities and can provide a more nurturing environment in comparison to mainstream schools, where children may be more vulnerable to marginalisation and victimisation (Warnock, 2005). In support of these suggestions, children with SEN have been found to express poorer social skills (Tur-Kaspa, 2002) and experience lower levels of social support (Martinez, 2006;Wilson, 2007) and more stigmatisation/peer victimisation (Cosden et al, 1999;Dykens, 2000), in comparison to typically developing children.…”
Section: Psychosocial Adjustment Associated With Special Educational mentioning
confidence: 98%
“…The association with calculation disorders at junior secondary schools seems to be an additional risk factor for lower global self-esteem, experience or perception of a lower social support (by the classroom, parents and friends), higher attention defi cit, higher emotional and depression symptoms, and higher school maladjustment. [48,49] Reading diffi culties Maughan et al's [50] research was conducted on children with persistent reading diffi culties under the 6th percentile, children who were therefore very similar to those with a diagnosis of dyslexia. They also found that attention defi cit in comorbidity plays a signifi cant role in connecting the correlation with psychopathology, especially the externalizing one (e.g., delinquency).…”
Section: Dyslexiamentioning
confidence: 99%